A dual-perspective analysis of the hospital and payer-borne burdens of selected in-hospital surgical complications in low anterior resection for colorectal cancer. Issue 2 (15th March 2019) - Ammann, Eric M.; Goldstein, Laura J.; Nagle, Deborah; Wei, David; Johnston, Stephen S.
ABSTRACT: Objectives : The economic burden of surgical complications is borne in distinctly different ways by hospitals and payers. This study quantified the incidence and economic burden – from both the hospital and payer perspective – of selected major colorectal surgery complications in patients undergoing low anterior resection (LAR) for colorectal cancer. Methods : Retrospective, observational study of patient undergoing LAR for colorectal cancer between 1/1/2010 and 7/1/2015. Analyses were replicated in two large healthcare administrative databases: Premier (hospital discharge and billing data; hospital perspective) and Optum (insurance claims data; payer perspective). Multivariable analyses evaluated the association between infection (surgical site or bloodstream), anastomotic leak, and bleeding complications and the following outcomes: hospital length of stay (LOS), non-home discharge, 90-day all-cause readmission, index admission costs to the hospital, index admission payer expenditures, and index admission +90-day post-discharge payer expenditures. Results : 9, 738 eligible LAR patients were included (7, 479 in Premier; 2, 259 in Optum). Overall, the incidences of infection, anastomotic leak, and bleeding complications were 6.4%, 10.6%, and 10.9%, respectively, during the index hospitalization. Each complication was associated with statistically significant longer LOS, higher risk of non-home discharge, higher risk of 90-day readmission, greater costs to the hospital, and higher payer expenditures. Conclusions : In-hospital infection, anastomotic leak, and bleeding were associated with a substantial economic burden, for both hospitals and payers, in patients undergoing LAR for colorectal cancer. This study provides information which may be used to quantify the potential economic value and impact of innovations in surgical care and delivery that reduce the incidence and burden of these complications.